Hambatan dan Strategi dalam Pendidikan Inklusi Studi Kasus di SLB ABC Melati Aisyiah - Nadia Saputri Daulay; Raditya Balqis; Siti Fatimah Sari Ritonga; Putri Damayanti Siahaan; Gabriel Febrianto Sinaga; Muhammad Rajali; Lili Tansliova (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study discusses the obstacles and strategies in inclusive education. The main problem in this study is to analyze the obstacles and strategies of deaf and mentally retarded children. Deafness is a condition of hearing loss, where children who experience it have difficulty or decreased ability to hear. Mental retardation is an individual who significantly has below average intelligence or experiences intellectual disabilities. This study was conducted at the ABC Melati Aisyiah Special School. This study uses a qualitative research method, and the data collection techniques are observation, in-depth interviews and documentation. The results of the study found obstacles and strategies that teachers need to implement appropriate strategies to overcome these obstacles. One strategy that can be done is to use media and learning aids that are in accordance with the characteristics of deaf students. Obstacles and strategies of teachers of mentally retarded children are lack of student focus during class lessons. Several factors that cause lack of concentration include their greater interest in games, delays in intellectual development, and disturbances from the noisy classroom environment.